Factorial experimental design for superabsorbent carbonaceous polymer through inverse suspension polymerization method - S. N. Ainda, Mazlan; Saidatul Shima, Jamari (IOP Publishing, 2019)
This paper studies on the effect of synthesis parameters towards the performance of superabsorbent carbonaceous polymer (SPC) via inverse suspension polymerization method. The SPC consists of acrylic acid, acrylamide, and carbon filler. In this work, four independent factors (synthesis parameters) i.e. the content of carbon filler, the content of initiator, the content of crosslinker and reaction temperature that affecting the water absorbency of SPC was investigated. A 24 full factorial design was used to investigate the effect of independent factors as well as the interaction factors on the water absorbency of SPC. Apart from reaction temperature, other factors were shown to have the significant effect on the water absorbency of SPC. The results showed the order of significance: initiator's content > crosslinker's content > carbon filler's content > reaction temperature. Meanwhile, interaction factor of carbon filler's and crosslinker's content had the strongest effect on the water absorbency amongst the other interactions. The highest water absorbency of the SPC was achieved at the conditions (filler's content (A): 0.05wt%; initiator's content (B): 0.10wt%; crosslinker's content (C): 0.001wt%, and reaction temperature: 70°C).